The Composition and Relative Chronology of Dynasties 16 and 17 in Egypt - Mahieu, Bieke (Antiguo Oriente, 2024)
The composition of Dynasties 16 and 17 is still a matter of debate. On the basis of onomastic, prosopographic, topographic, and king lists’ data, the present article identifies the fifteen kings who ruled in Dynasty 16 at Thebes as Sekhemra-shedtawy Sobekemsaf I, Sekhemra-sementawy Djehuty, Sekhemra-seusertawy Sobekhotep VIII, Sekhemra-sankhtawy Neferhotep III, Sankhenra Mentuhotepi, Sewadjenra Nebiryrau I, Nebiryrau II, Semenenra (Mentu-user?), Seuserenra Bebiankh, Sekhemra-wadjkhau Sobekemsaf II, Sekhemra-heruhirmaat Intef V, Sekhemra-wepmaat Intef VI, Nubkheperra Intef VII, Seqenenra Tao, and Wadjkheperra Kamose. It is proposed that Dynasty 17 ruled from Abydos during the second part of Dynasty 16 and was comprised of Useribra Seneb-Kay, Menkhaura Snaaib, Sekhemra-wahkhau Rahotep, Sekhemra-neferkhau Wepwawetemsaf, Sekhemra-khutawy Pantjeny, Senakhtenra Ahmose I, and eleven kings who remain unidentified. A relative chronology for the dynasties and their kings is proposed.